The Effect of Core Tax System, Tax Socialization, and Tax Morale on Tax Compliance With Tax Awareness As A Moderating Variable - Amalia, Silviyani Suci; Tanjung, Juita (SENTRALISASI, 2025)
The purpose of this investigation is to examine how the following factors affect tax compliance: core tax system, tax socialization, and tax morale, with tax awareness as a moderating variable. This research was carried out at the Kantor Pelayanan Pajak (KPP) Pratama Jakarta Kebayoran Baru Dua using primary data from a survey, which was then analyzed using SmartPLS. Findings from the study suggest that the Core Tax System, Tax Socialization, and Tax Morale exert a favorable and substantial influence on Tax Compliance, with Tax Awareness strengthening the relationship between these variables. However, it weakens the connection between the Core Tax System and Tax Compliance. Internal factors of Tax Morale, influenced by societal conventions, faith in the government, and perceptions of justice, along with the Core Tax System and Tax Socialization as external factors, play an essential part in improving Tax Compliance. In terms of Tax Awareness, it weakens the correlation between the Core Tax System and Tax Compliance, indicating that system improvements alone are insufficient without enhancing awareness and Tax Morale. This is because the sustainability of long-term compliance depends more on the development of Tax Morale and awareness through continuous education and the enforcement of strict yet fair sanctions, thereby ensuring that the motivation to comply remains ingrained in taxpayers.